Aligning Health Occupation Students for Valuable Interprofessional Learning: Evaluating Program Structure, Resources, and Student Experiences in a Regional Clinical Setting - Edwards, Emma; Lyons, Nikki; Edwards, Lisa; Hitch, Danielle; Kelly, Mark; Dow, Jane; Kavanagh, Laura; King, Olivia (International Journal of Practice-based Learning in Health and Social Care, 2024)
Developing Inter-Professional Education (IPE) programs for undergraduate healthcare students poses multiple complex challenges, in both university and workplace settings. These challenges can limit the widespread implementation of IPE, despite research demonstrating its potential impact on improving knowledge about other professions roles, collaborative practice, and inter-professional identity. The aim of this study was to provide an overview of an IPE program delivered in a regional health service during clinical placements and evaluate student perceptions of its value to their learning. Students from fourteen disciplines (n=136 across eight workshops) completed a retrospective mixed methods survey. Students particularly valued the following aspects of the IPE program: clinical simulation, structured approach to communication and timely multi-source feedback. Inter-professional learning which enabled opportunities to learn with, from or about students was highly valued.